Waste Management Analysis Of South Tangerang City (Alternative Review of Solving Waste Management Problems in Urban Areas) - Ahmad Hadian Pratama Hamzah; Yustiati Yustiati; Nurhasanah Nurhasanah; Subekti Nurmawati (Innovative: Journal Of Social Science Research, 2023)
South Tangerang City as an Autonomous city formed in 2006 continues to develop in various fields. The well-developed economic activities of South Tangerang City have also caused an increase in the amount of waste generated from community activities in addition to population growth. Hygiene problems, especially garbage, are still a serious problem in South Tangerang. The responsibility of waste management is not only with the government but also the responsibility of the community. Everyone responsible for managing household waste or a type of household waste is obliged to reduce or handle waste in an environmentally mindful way.